Extrapolating stereotypical information on sexual orientation from race categories: the case of black and asian men - Carnaghi, A. (2020)
The current research analyzed whether race categories concerning Black and Asian men could lead to extrapolative inferences concerning the sexual orientation of these category members (i.e., ESOS, extrapolative sexual orientation stereotyping). Study 1 assessed perceived cultural-based ESOS and showed that Black men, compared to Asian men, were thought to be more heterosexual than gay men. Study 2 assessed participants’ own ESOS and showed that Black men were conflated with heterosexual men and to a greater extent than Asian men, although Asian men were not assimilated to gay men. Black and White men were equally stereotyped as heterosexual men, thus suggesting a drop in the perceived heterosexuality of Asian men rather than an enhancement of the perceived heterosexuality of Black men. Study 3 confirmed that Black men were perceived as more masculine, less feminine and more heterosexual than Asian men, while no difference was found between the two racial categories in the perceived homosexuality. The enhanced perception of femininity of Asian compared to Black men was associated with a decreased perception of Asian compared to Black men as heterosexual. Together, results suggest that the category of Asian and Black men worked as the basis for inferring the sexual orientation of these group members. These racial categories affected the inferred heterosexuality and less, if not somewhat elusively, the inferred homosexuality of Asian and Black men. Results were discussed with respect to research concerning the extrapolative stereotyping and gender-inversion stereotypes of gay men.